How Twitter interacts with Society - Insight into an emerging field of research (KULT_online, 2014)
In 31 articles the anthology "Twitter and Society" provides an international and interdisciplinary overview of the scientific examination of the microblogging service Twitter and its interaction and connections with society. Alongside articles dealing with the theoretical foundations of Twitter research and a large selection of case studies, the volume presents various analytical methods and discusses the accompanying research-related challenges.